Electrochemical detection of environmental pollutants and food contaminants - Muhammad Zafir Mohamad Nasir (2018)
With a rapidly changing global environment, the evolution of techniques and methodologies has to keep up with advancement in technology. Electrochemistry has been a useful and effective technique in sensing applications. The versatility of electrochemical techniques, coupled with emerging new materials and technology, has enabled numerous methodologies to be developed for the detection of environmental pollutants and food contaminants with enhanced sensitivity and selectivity. In this thesis, graphite and transition metal dichalcogenides (TMDs) were identified as the nanomaterials to provide an alternative material for electrochemical sensing applications. The simultaneous detection of several mycotoxins on edge plane pyrolytic graphite (EPPG) was successfully demonstrated with high degree of selectivity and sensitivity. The limitations of TMDs in electrochemical applications were studied afterwhich the performance was optimized for the fabrication of an enzyme biosensor system for the detection of organophosphate pesticide with high sensitivity and low limits of detection. The incorporation of new technology and ideas, such as 3D printing and single particle detection, with electrochemical techniques were demonstrated. With the use of screen-printed electrodes, the detection of defined monodispersed silver nanoparticles and lipid liposomes were successfully demonstrated using impact electrochemistry. 3D printed metal electrodes modified with gold have proven to be a promising technique for the detection of nitroaromatic and phenolic pollutants which outperformed that of conventional glassy carbon electrode. The proof-of-concept applications open up limitless possibilities for the potential advancements in the use of nanomaterials and emerging technology for electrochemical sensing applications.